The Baikal-GVD neutrino telescope: search for high-energy cascades - Allakhverdyan V.A.; Avrorin A.D.; Avrorin A.V.; Aynutdinov V.M.; Bannasch R.; Bardаčová Z.; Belolaptikov I.A.; Borina I.V.; Brudanin V.B.; Budnev N.M.; Dik V.Y.; Domogatsky G.V.; et al. (Italy, 2025)
Baikal-GVD is a neutrino telescope currently under construction in Lake Baikal. GVD is formed by multi-megaton subarrays (clusters). The design of Baikal-GVD allows one to search for astrophysical neutrinos already at early phases of the array construction. We present here preliminary results of a search for high-energy neutrinos with GVD in 2019-2020
37th International Cosmic Ray Conference (ICRC2021)